Improving The Speaking Skills of The Tenth-Grade Students at SMA Negeri 1 Sindue Through the Song Interpretation Method - Fadila Palmai; Abd. Kamaruddin; Moh. Abraham Akbar Eisenring; Zarkiani Hasyim (MASI Mandiri Edukasi, 2025)
Many learners continue to struggle with English speaking skills, particularly in achieving accuracy and clarity of comprehension. This study aimed to investigate the effect of the Song Interpretation Method on enhancing the speaking performance of tenth-grade students at SMA Negeri 1 Sindue during the 2025/2026 academic year. The research focused on two main aspects of speaking ability: accuracy and comprehensibility. A quantitative approach was implemented through a quasi-experimental design involving pre-test and post-test control groups. The sample consisted of two classes selected through random sampling, with one designated as the experimental group and the other as the control group. Statistical analysis was conducted using SPSS software, and the Mann–Whitney U Test was employed to assess the differences between the two groups. The findings indicated an Asymp. Sig. (2-tailed) value of 0.035, which is lower than 0.05, signifying a significant difference between the post-test scores of the groups. Consequently, the alternative hypothesis (Ha) was accepted, confirming that the Song Interpretation Method substantially enhanced students’ speaking proficiency, particularly in terms of accuracy and comprehensibility. These findings suggest that integrating songs into English instruction can foster communicative competence, increase classroom interaction, and motivate learners in EFL contexts.